The Brain and the Bladder: Forebrain Control of Urinary (In)Continence - Tish, Margaret M.; Geerling, Joel C. (Frontiers in Physiology, 2020)
Neural circuits extending from the cerebral cortex to the bladder maintain urinary continence and allow voiding when it is socially appropriate. Injuries to certain brain regions produce a specific disruption known as urge incontinence. This neurologic symptom is distinguished by bladder spasticity, with sudden urges to void and frequent inability to maintain continence. The precise localization of neural circuit disruptions responsible for urge incontinence remains poorly defined, partly because the brain regions, cell types, and circuit connections that normally maintain continence are unknown. Here, we review what is known about the micturition reflex circuit and about forebrain control of continence from experimental animal studies and human lesion data. Based on this information, we hypothesize that urge incontinence results from damage to a descending pathway that normally maintains urinary continence. This pathway begins with excitatory neurons in the prefrontal cortex and relays subcortically, through inhibitory neurons that may help suppress reflex micturition during sleep and until it is safe and socially appropriate to void. Identifying the specific cell types and circuit connections that constitute the continence-promoting pathway, from the forebrain to the brainstem, will help us better understand why some brain lesions and neurodegenerative diseases disrupt continence. This information is needed to pave the way toward better treatments for neurologic patients suffering from urge incontinence.